Universal Testing Machine Electro-Mechanical 50kN - SERC, Pusat Penyelidikan Sains & Kejuruteraan (Science & Engineering Research Centre, 2016)
Applications: Test Type: Suitable for static tests, such as tension test, bending test (3 point & 4-point), compression test. Test Result: Suitable to be used to determine Modulus of Elasticity, Yield Stress, Tensile Strength, Load at break, Modulus of Rupture. Specimen type: Suitable for static testing of composites, plastics, metal, wood, adhesive, elastomer.